Loss of prolyl hydroxylase‐2 in myeloid cells and T‐lymphocytes impairs tumor development. Issue 4 (29th August 2013) - Mamlouk, Soulafa; Kalucka, Joanna; Singh, Rashim Pal; Franke, Kristin; Muschter, Antje; Langer, Anika; Jakob, Christiane; Gassmann, Max; Baretton, Gustavo B.; Wielockx, Ben
<x xml:space="preserve">Abstract</x> The tumor microenvironment plays a pivotal role during cancer development and progression. The balance between suppressive and cytotoxic responses of the tumor immune microenvironment has been shown to have a direct effect on the final outcome in various human and experimental tumors. Recently, we demonstrated that the oxygen sensor HIF‐prolyl hydroxylase‐2 (PHD2) plays a detrimental role in tumor cells, stimulating systemic growth and metastasis in mice. In our current study, we show that the conditional ablation of PHD2 in the hematopoietic system also leads to reduced tumor volume, intriguingly generated by an imbalance between enhanced cell death and improved proliferation of tumor cells. This effect seems to rely on the overall downregulation of protumoral as well as antitumoral cytokines. Using different genetic approaches, we were able to confine this complex phenotype to the crosstalk of PHD2‐deficient myeloid cells and T‐lymphocytes. Taken together, our findings reveal a multifaceted role for PHD2 in several hematopoietic lineages during tumor development and might have important implications for the development of tumor therapies in the future.